The cost and cost-effectiveness of integrating wasting prevention into screening in facility- and community-based platforms in Burkina Faso and Mali - Brander, Rebecca L.; Puett, Chloe; Becquey, Elodie; Leroy, Jef L.; Ruel, Marie T.; Sessou, Fidele Eric; Huybregts, Lieven (2024)
Objectives: The release of the new WHO guideline on the prevention and treatment of child wasting identified a dearth of rigorous evidence on the cost-effectiveness of wasting-related interventions, and especially so for interventions that integrate prevention into screening. We estimated the cost and cost-effectiveness of integrating prevention interventions - behavior change communication (BCC) and small quantity lipid-based nutrient supplements (SQ-LNS) - into a facility-based platform in Burkina Faso with enhanced BCC and a community-based platform in Mali with standard BCC.